MENINGKATKAN KEMAMPUAN BERHITUNG MELALUI PERMAINAN TRADISIONAL - Marwiyah, Eneng Sri Susilawati, Hadi Sutiawan (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This classroom action research aims to improve numeracy skills through traditional games in children aged 5-6 years in PAUD BIna Ananda, Binuang district, the method used in this research is the Lewin model. PTK is carried out as an effort to overcome problems that occur in the classroom. This method is carried out in four stages, namely planning, implementation, observation and reflection. The subjects of observation were 10 students aged 5-6 years at PAUD Bina Ananda, and the object of this research was to improve numeracy skills in children aged 5-6 years. Data collection techniques used observation and documentation and data analysis used descriptive qualitative, the indicators set were a minimum of 75% of the 10 children studied had good numeracy skills. This research was conducted in two cycles. The results of the research show that the numeracy skills of children aged 5-6 years at PAUD Bina Ananda have shown an increase. The increase in understanding the concept of numbers in children aged 5-6 years at the time of pre-research showed results of 35% and experienced an increase in the first cycle of 60.6%. Because the value obtained had not reached the predetermined criteria, the next action was carried out, namely cycle II action and experienced a good increase with a score of 83.1%. Because the predetermined results had been achieved, the research was stopped because it had reached the success criteria